Designing English For Specific Purpose Materials: A Preliminary Product for Informatics Engineering Context: Merancang Materi Bahasa Inggris Untuk Tujuan Khusus: Produk Awal untuk Konteks Teknik Informatika - Nimasari, Elok Putri; Mufanti, Restu; Gestant, Rohfin Andria (Universitas Muhammadiyah Sidoarjo, 2019)
English for Informatics Engineering (EIE, hereafter) is significantly requisite for tertiary students. Since EIE is one of English for Specific Purposes (ESP, hereafter) branches, it has particular inescapable characteristics. Teaching materials for EIE should be composed and delivered based on those attributes. Although the materials can be adapted from various resources, developing materials for EIE should definitely follow pedagogical standardized procedures. This article aims to present how material development for EIE is designed based on need analysis results described in a previous research (Nimasari, 2018) and developed according to a specific ESP teaching approach. This current study is a further examination of need analysis results implemented in a coursebook for Informatics Engineering students in a private university in Indonesia. As a part of research and development project research, this study focuses on developing preliminary form of product that includes a prototype of EIE coursebook development. A text-based instruction is utilized as a basis approach to design the EIE material. The results of this preliminary product are four lessons of EIE materials. While one lesson will be presented thoroughly in the discussion, the other three lessons will be attached in the appendix.